Makna Al- ‘Afw dalam Surah Al-Baqarah Ayat 219 Perspektif Tafsīr Al-Marāghī - Hidayah, Arbiatun (Lembaga Yasin AlSys, 2023)
The meaning of al-'Afw in the Qur'an which has the same word but differs from its meaning. al-'Afw which many people understand as forgiveness. In contrast to the meaning of al-'Afw contained in surah Al-Baqarah verse 219 where al-'Afw is defined as excess. The qualitative method is a method that focuses on the data the author obtained from previous researchers. This research also belongs to the library research method, namely Primary Data Sources; used by the author namely the Al-Qur'an Mushaf and the book of Tafsir al-Marāghī, and Secondary Data Sources; The materials used include works or literature in the form of research results, journal articles, books, the internet, and so on that have a correlation with the theme of this research and can strengthen and support the completeness of primary data. As for the results of this study, according to al-Marāghī al-'Afw it has the meaning of excess of basic needs, namely what they have to spend from their possessions as their obedience to Allah's commands. The Qur'an mentions the word as much as possible or more so that each people can determine independently according to their respective economic capabilities. Related to the interpretation of Ahmad Musthofa al-Marāghī explaining the function of the meaning of al-'Afw in surah Al-Baqarah verse 219. In addition, because humans are social beings, the writer feels the need to discuss the meaning of al-'Afw in the social context of society.